Juvenile homicide offending: first-time offense or escalation of criminal offending? - Baglivio, Michael T. (Routledge handbook of homicide studies, 2024)
Juveniles perpetrate approximately 8% of all U.S. homicides. While prior studies have examined differences between juvenile homicide offenders (JHO) and other youth offenders, little research has examined differences among JHO. This chapter explores sex and race/ethnicity differences among a multiyear statewide sample of over 1,800 JHO. Further, the chapter assesses differences between those 40% of JHO for whom the homicide was their first arrest, JHO with minimal prior offending, and JHO who had chronic juvenile offending patterns prior to their homicide arrest. Multinomial models explore which demographic, criminal history, school-related factors, and prominent risk factors distinguish these groups of JHO from one another. Findings reveal JHO to be a heterogeneous group.